Influence of Gold Nano Particles on Dielectric Features A.C. Conductivity and Dielectric Breakdown Strength of PbO-B2O3-SeO2:Ho2O3 Glass Ceramics. (1st August 2022) - Siva Sesha Reddy, A.; Kostrzewa, M.; Purnachand, N.; Ingram, A.; Sahaya Baskaran, G.; Venkatramaiah, N.; Ravi Kumar, V.; Veeraiah, N.
Abstract : The objective of this study is to report the results of dielectric properties and dielectric breakdown strength (DBS) of PbO-B2 O3 -SeO2 :Ho2 O3 (PBSH) glass ceramics as functions of Au2 O3 content and to correlate the results with spectroscopic properties. PBSH glass ceramics with traces of Au2 O3 were fabricated and characterized with different techniques that include positron annihilation spectroscopy (PAS). Several dielectric parameters and DBS were studied as functions of Au2 O3 concentration. Observed increase of ε′ with Au2 O3 content was attributed to a hike in the space charge polarization (scp) due to the increased concentration of structural imperfections. Dipolar relaxation phenomenon exhibited by electric moduli was analyzed using Cole-Cole plots. σ ac (a c, conductivity) showed an increasing tendency with Au2 O3 content. Such increase was attributed to the polaronic exchange between two structural groups of SeO2 . Inferences drawn from dielectric and DBS studies were found to be in agreement with different spectroscopic properties of these glass ceramics.